Development and Performance Evaluation of Coconut Scraper - NANDHU LAL A.M RASMI P.K; Dr. Sudheer K.P (Guide) (Tavanur 2017 Department of Food and Agricultural Process Engineering)
Development and Performance Evaluation of Coconut Scraper
Development and Performance Evaluation of Coconut Scraper